THE IMPORTANCE OF PHYSIOTHERAPY AND MASSAGE IN NURSING PRACTICE - Vokhidova Feruza Ganievna; Radjabova Markhabo Botirovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Physiotherapy and massage are integral components of holistic healthcare, promoting recovery, managing pain, and enhancing physical and mental well-being. In nursing practice, understanding these modalities enables nurses to collaborate effectively with physiotherapists, guide patients in rehabilitation, and provide supportive care. This article explores the significance of physiotherapy and massage in nursing, emphasizing their roles in improving patient outcomes and overall quality of life.